Creative positioning of children’s music school as a factor in the formation of the cultural space of a small town - Alikperov, Igor; Arzhannikova, Natalya (Managing of Culture, 2025)
Modern conditions dictate the active development of the creative economy, which is based on the creative potential of a person, his skills, abilities, talents, based on a modern technological complex and knowledge base. The creative economy provides opportunities for innovative modernization of the territory, contributes to the increase of its competitiveness. As a result, the city becomes attractive both for specialists in various fields of activity, business, tourists, and for the local community. Children's music school brings up a creative person with creative thinking, who will be useful for the development of the city, society. Residents of cities, especially small ones, who are able to find an unconventional approach to solving complex problems, are in demand in modern times. Offering a comprehensive education, including the development of cognitive abilities, encouraging self-expression, children's music school forms a cultural community. Directing, adjusting their activities in accordance with modern trends, these schools, as part of additional education, can offer city residents not only specialized education, but also participation in various events that satisfy the audience's demand for high-quality leisure. At the same time, cultural institutions, including children's music schools, need to think not only about the loyalty of the current audience, but also attract a new one. To do this, it is important not only to comply with state educational and cultural standards, but also to offer the audience original products (services) and effectively promote them in the socio-cultural space of the territory. This tool is called positioning, which is effectively used in marketing activities by well-known theater and concert organizations. The use of this tool by children's music schools allows solving not only management (marketing) problems, but also bringing educational and creative processes to a new level. In this regard, the authors substantiate the importance of using this tool in the activities of children's music schools, reveal the stages and principles of positioning, consider the experience of successful positioning by well-known cultural institutions and, using the example of the multi-product "Orchestral Adventures" in the Sukhoi Log Children's Music School, convincingly show the possibilities of positioning to increase the competitiveness of an organization.